Coaching: a reference model for the practice of nurse-leaders in the hospital context - Cardoso, Maria Lúcia Alves Pereira; Ramos, Laís Helena; D’Innocenzo, Maria (Revista da Escola de Enfermagem da USP, 2011)
The objectives of the present study was to evaluate the leadership of nurses by using the coaching strategy as a managerial tool, and identify, measure and analyze the acquisition of competencies from the view of nurse-coaches. This is a descriptive, cross-sectional, exploratory and field study that was performed using a quantitative approach. Situational Leadership was selected as the theoretical framework and the research instrument was submitted to statistical and content analyses and was applied on 11 nurse leaders of a large scale private general hospital located in São Paulo. The results showed that participants gained new knowledge, confirmed the Situational Leadership model as the recognized being a coach leader, with a style that is mainly aimed at tasks and people, according to the situation involved, and pointed out the following skills as determinant of coaches: communication, giving and receiving feedback, assigning and gaining power and having an influence. Finally, the attitudes reflected the practice of coaching.